Guidance on technical requirements for regulated food and feed product applications to establish the presence of small particles including nanoparticles - EFSA Scientific Committee; Simon More; Vasileios Bampidis; Diane Benford; Claude Bragard; Thorhallur Halldorsson; Antonio Hernández‐Jerez; Susanne Hougaard Bennekou; Kostas Koutsoumanis; Claude Lambré; Kyriaki Machera; Hanspeter Naegeli; et al. (EFSA Journal, 2021)
Abstract Following a mandate from the European Commission, EFSA has developed a Guidance on Technical Requirements (Guidance on Particle‐TR), defining the criteria for assessing the presence of a fraction of small particles, and setting out information requirements for applications in the regulated food and feed product areas (e.g. novel food, food/feed additives, food contact materials and pesticides). These requirements apply to particles requiring specific assessment at the nanoscale in conventional materials that do not meet the definition of engineered nanomaterial as set out in the Novel Food Regulation (EU) 2015/2283. The guidance outlines appraisal criteria grouped in three sections, to confirm whether or not the conventional risk assessment should be complemented with nanospecific considerations. The first group addresses solubility and dissolution rate as key physicochemical properties to assess whether consumers will be exposed to particles. The second group establishes the information requirements for assessing whether the conventional material contains a fraction or consists of small particles, and its characterisation. The third group describes the information to be presented for existing safety studies to demonstrate that the fraction of small particles, including particles at the nanoscale, has been properly evaluated. In addition, in order to guide the appraisal of existing safety studies, recommendations for closing the data gaps while minimising the need for conducting new animal studies are provided. This Guidance on Particle‐TR complements the Guidance on risk assessment of nanomaterials to be applied in the food and feed chain, human and animal health updated by the EFSA Scientific Committee as co‐published with this Guidance. Applicants are advised to consult both guidance documents before conducting new studies.